2017
DOI: 10.5604/12321966.1233568
|View full text |Cite
|
Sign up to set email alerts
|

Human infections caused by free-living amoebae

Abstract: Introduction. Among free-living amoebae that are widely distributed in nature only four genera/species are known as agents of human infections: Acanthamoeba spp., Naegleriafowleri, Balamuthia mandrillaris and Sappiniapedata. These amoebae are not well adapted to parasitism, and could exist in the human environment without the need for a host. Infections due to these amoebae, despite low morbidity, are characterized by relatively high mortality rate and pose serious clinical problems. Objectve. This review stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 43 publications
2
73
0
5
Order By: Relevance
“…are the most common free-living amoebae have been isolated from a wide range of environments particularly water. Free-living amoebae have been reported to feed by phagocytosis on bacteria, fungi, and algae (Król-Turmińska and Olender, 2017;Chen et al, 2018). According to the previous reports (Scheid and Schwarzenberger, 2012;Yousuf et al, 2017), Acanthamoeba might serve as an environmental reservoir for viruses living in the same environment, such as mimivirus, coxsackievirus and adenovirus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…are the most common free-living amoebae have been isolated from a wide range of environments particularly water. Free-living amoebae have been reported to feed by phagocytosis on bacteria, fungi, and algae (Król-Turmińska and Olender, 2017;Chen et al, 2018). According to the previous reports (Scheid and Schwarzenberger, 2012;Yousuf et al, 2017), Acanthamoeba might serve as an environmental reservoir for viruses living in the same environment, such as mimivirus, coxsackievirus and adenovirus.…”
Section: Discussionmentioning
confidence: 99%
“…are the most common free-living protozoa, isolated from public water supplies, swimming pools, bottled water, distilled water bottles, ventilation ducts, the water-air interface, air-conditioning units, soil, beaches, vegetables, air, surgical instruments, and contact lenses, indicating the ubiquitous nature of these organisms (Cruz and Rivera, 2014;Todd et al, 2015;Al-Herrawy et al, 2015). Acanthamoeba species can cause various diseases such as keratitis and granulomatous amoebic encephalitis, which is often fatal in immune-compromised as well as immunocompetent patients (Król-Turmińska and Olender, 2017). The possible mode of transmission includes direct contact of contaminated water, inhalation of cysts or trophozoites of Acanthamoeba carried by the wind through the respiratory tract, improper contact lens-care practices, or direct skin contact by traumatic injection or entry through preexisting wounds or lesions.…”
Section: Introductionmentioning
confidence: 99%
“…A previous report indicated that only a few drugs have demonstrated in vitro activity against Acanthamoeba and have resulted in the successful treatment of a few patients: azoles, rifampicin, pentamidine, sulfadiazine, azithromycin, caspofungin, etc. [ 13 ]. The clinical usefulness of subclassification of Acanthamoeba also remains unknown at this time.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of immunodeficiency, Acanthamoeba can cause a central nervous system infection called granulomatous amebic encephalitis or may disseminate to multiple organ systems. Disseminated infections usually occur in solid organ transplant recipients, AIDS patients, or patients with hematological malignancies (4). Acanthamoeba infections have rarely been reported to occur in lung transplant recipients, and to our knowledge, only nine other cases have been reported in this setting (5,6).…”
mentioning
confidence: 81%